2022
DOI: 10.2196/36941
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of the COVID-19 Pandemic on Reddit: Comparative Natural Language Processing Study of the United States, the United Kingdom, Canada, and Australia

Abstract: Background Since COVID-19 was declared a pandemic by the World Health Organization on March 11, 2020, the disease has had an unprecedented impact worldwide. Social media such as Reddit can serve as a resource for enhancing situational awareness, particularly regarding monitoring public attitudes and behavior during the crisis. Insights gained can then be utilized to better understand public attitudes and behaviors during the COVID-19 crisis, and to support communication and health-promotion messagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…According to a study, a correlation has been observed between such data and the incidence of COVID-19, with the data peaking 10-14 days before the incidence peak [8]. Other social media platforms like Facebook [9] and Reddit [10] can also provide valuable data for real-time disease surveillance for EIDs. Our study highlights the potential of internet search engines and social media data for real-time disease surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, a correlation has been observed between such data and the incidence of COVID-19, with the data peaking 10-14 days before the incidence peak [8]. Other social media platforms like Facebook [9] and Reddit [10] can also provide valuable data for real-time disease surveillance for EIDs. Our study highlights the potential of internet search engines and social media data for real-time disease surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Biester et al 20 examine changes in topics in mental health-related subreddits using LDA and changes in patterns of interactions between users using social network analysis Other studies on automated topic detection also focus on mental health subreddits. 21 , 22 However, none of the aforementioned studies that took a machine learning (ML) and AI-assisted path for the analysis of subreddits focused on pregnant users on Reddit.…”
Section: Introductionmentioning
confidence: 99%